The Development Perspectives of Syunik’s Mining Industry in the Context of Solving the Socio-Economic and Environmental Problems of RA - Gharibyan, Grigor; Hovakimyan, Arno (Bulletin of Yerevan University G: Economics, 2016)
The current state and the development perspectives of Syunik’s mining industry are closely studied in the article. The main ways of further development of the mining industry are revealed. We have estimated the socioeconomic (unemployment rate, GDP, taxes, etc.) and environmental consequences of the possible development of Syunik’s mining industry.